A qualitative study on awareness, attitudes, behaviors and social adaptation of mothers of children with cystic fibrosis - GÖKDEMİR, YASEMİN; ERDEM ERALP, ELA; ERGENEKON, ALMALA PINAR; KARADAĞ, BÜLENT TANER; KARAVUŞ, MELDA (My University, 2023)
Objectives: Cystic Fibrosis (CF) may affect the whole life of the family and social adaptation is very important for the management. Aim of this study is to evaluate awareness, attitudes, behaviors, and social adaptation of mothers of children with CF. Methods: Our qualitative study was carried out in April 2022 with 11 mothers of children admitted to a CF center in İstanbul, Türkiye. For data collection a semi-structured question guide was applied using in-depth interview technique. Thematic analysis method was used in analysis of the data. The ethics committee approval was obtained. Results: Most mothers noticed the disease in the presence of symptoms such as salty skin, frequent productive coughing, and fever attacks. Majority were not aware of the cause, some even thinking that it could be due to an accident or prolonged delivery. All parents adjusted their whole lives according to their children and their social life was limited after the diagnosis. They abided by hygienic rules, seldom spent time outside home, particularly avoided crowded areas. While most mothers expressed that their family relations were strengthened, and they were supported psychosocially, some mothers could not get the understanding and support they expected. Many of the participants received professional psychological support to cope with this situation. The disease had a negative impact on the education life of children; in addition to that families had difficulties due to the economic burden of the treatment. Majority stated the Covid-19 pandemic did not affect them so much, since their life was already limited. Their advice for the parents of newly diagnosed children were to be strong. Conclusion: CF affects the lives of families in many ways, especially psychosocially and economically. Despite all the difficulties, the mothers could cope with life and became somewhat resilient. Awareness of CF should be raised in society and psychosocial support should be provided to caregivers.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (Med); Clinical Medicine (Med)